Impact of mind‐wandering on visual information processing while driving: An electrophysiological study. Issue 2 (7th December 2020) - Pepin, Guillaume; Fort, Alexandra; Jallais, Christophe; Moreau, Fabien; Ndiaye, Daniel; Navarro, Jordan; Gabaude, Catherine
Summary: Mind‐wandering (MW) has a negative impact on tasks requiring sustained and divided attention like driving. During MW, drivers experience perceptual decoupling. As driving is mainly a visual activity, it would seem to be appropriate to evaluate stages of visual information processing impaired during MW, using event‐related potential techniques. The aim of the present study was to investigate how the level of attention devoted to driving impacted visual information processing and reaction time. The findings showed reductions in visual N1 and P3 amplitudes while driving and longer reaction times during periods of self‐reported MW. This suggests that drivers can become detached from their environment by redirecting their attention to their personal thoughts and some of their cognitive resources may be consumed to feed internal trains of thought. In the future, investigating off‐task characteristics might be useful in better understanding the impact of MW in car crashes.